Current situation and countermeasures of traditional Chinese medicine resource distribution: a case study of Wuyi County in China - Zhu, Xiao; Zhang, Zhiqiang; Xu, Lingjian; Zhong, Xiayuan (Frontiers in Public Health, 2025)
ObjectiveTo investigate the current status of Traditional Chinese Medicine (TCM) resource development within Chinese counties and identify enforceable strategies.MethodsWuyi County was adopted as a case study, analyzing the distribution of TCM resources within the county. Based on the TCM development models employed in other counties, this study proposed the “Wuyi mode,” which integrates “medical consortiums + medical communities + specialty alliances + shared Chinese medicine pharmacies.” Meanwhile, the model was applied in practice, and its effectiveness was verified.ResultsThe study provides novel insights into addressing the issue of uneven distribution of TCM resources at the county level and contributes to the establishment of a new model for TCM development.ConclusionThe “Wuyi mode” offers a valuable framework that may inform the development of TCM in other counties across China and potentially serve as a reference for TCM development globally.